2012
DOI: 10.3928/1081597x-20120124-02
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes and Safety of a Small Diameter Intrastromal Refractive Inlay for the Corneal Compensation of Presbyopia

Abstract: The intracorneal refractive inlay (Invue Lens) seems to be an effective surgical method for the corneal compensation of presbyopia in emmetropes aged between 45 and 60 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 16 publications
0
21
0
4
Order By: Relevance
“…10 This has been a concern also for the implantation of intracorneal inlays for the corneal compensation of presbyopia. 10,11 In our cases, we created an intracorneal pocket of 6.5 mm in diameter (about half the diameter of the cornea) in which we injected silicone oil (barrier); this approach leaves the peripheral corneal (outside the 6.5 mm) intact, and thereby the transport of glucose at the anterior cornea although influenced, it is not completely stopped, which allowed for suboptimal corneal nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…10 This has been a concern also for the implantation of intracorneal inlays for the corneal compensation of presbyopia. 10,11 In our cases, we created an intracorneal pocket of 6.5 mm in diameter (about half the diameter of the cornea) in which we injected silicone oil (barrier); this approach leaves the peripheral corneal (outside the 6.5 mm) intact, and thereby the transport of glucose at the anterior cornea although influenced, it is not completely stopped, which allowed for suboptimal corneal nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…L'approche cornéenne est séduisante car elle présente un minimum de risques, particulièrement en comparaison à la chirurgie endoculaire (risque d'endophtalmie aiguë sur un oeil parfaitement voyant). Il existe à ce jour plusieurs techniques de chirurgie cornéenne proposées aux patients presbytes : la monovision ou « bascule », les inlays intracornéens, l'intracor (intrastromal femtosecond treatment) et le presbylasik [2][3][4][5][6][7][8][9][10][11][12][13][14]. Ce dernier se divise en deux techniques capables de réaliser « une cornée multifocale » par chirurgie réfractive cornéenne.…”
Section: Discussionunclassified
“…Invue lens (Biovision) is another corneal inlay which is implanted inside a corneal pocket of the nondominant eye created using a mechanical microkeratome. Bouzoukis et al [10] reported improving near visual acuity with 20/32 UNVA in 98% of the patients.…”
Section: The Raindrop Near Vision Corneal Inlay Formerly Known As Thmentioning
confidence: 97%
“…Compared to the mechanical technique, the FS laser makes tunnel creation faster, easier and more reproducible and offers precise tunnel dimensions (width, diameter and depth) compared to manual techniques [7][8][9][10][11][12][13][14][15]. Thus, FS-assisted intracorneal pocket creation could increase the precision of the inlay position and result in better final visual outcomes besides improving the safety of the procedure.…”
Section: Surgical Technique Of Intracorneal Inlay Implantationmentioning
confidence: 99%
See 1 more Smart Citation